Hydrolysis of dimethyl terephthalate to terephthalic acid on Nb‐modified HZSM‐5 zeolite catalysts. Issue 7 (2nd February 2022) - Guo, Bao; Liu, Jidong; Tang, Shixiong; Liu, Yida; Tian, Zenan; Lv, Jianhua
Abstract: BACKGROUND: Whether waste polyethylene terephthalate (PET) can be effectively recycled is one of the main challenges of the current environmental problems. The hydrolysis of dimethyl terephthalate (DMT) to terephthalic acid (TPA) over Nb‐modified HZSM‐5 zeolite was studied. Nb/HZSM‐5 zeolites with different loadings were prepared and characterized by X‐ray diffraction, X‐ray photoelectron spectroscopy, scanning electron microscopy, NH3 ‐temperature programmed desorption and pyridine adsorption infrared spectroscopy. The effects of different reaction conditions on the conversion of DMT and TPA yield were investigated. RESULTS: The yield of TPA strongly depends on the reaction conditions and the loading of Nb. The niobium phase exists in the form of Nb2 O5 on the zeolite and interacts with the surface of HZSM‐5 to produce the active site of Brønsted acid. The yield of TPA is closely related to the concentration of Brønsted acid sites. On 0.6Nb/HZSM‐5 catalyst, the yield of TPA is highest, at about 94%. CONCLUSION: Nb/HZSM‐5 catalyst has excellent catalytic activity and high stability for DMT hydrolysis. In addition, the product TPA prepared in this study can be directly applied to the current PET production supply chain, providing a promising catalytic route. © 2022 Society of Chemical Industry (SCI).